14. Cerebellar direct current stimulation modulates hand blink reflex: Implications for defensive behavior in humans. Issue 12 (December 2017) - Bocci, T.; Ferrucci, R.; Barloscio, D.; Parenti, L.; Cortese, F.; Priori, A.; Sartucci, F.
Abstract : The cerebellum is involved in a wide number of integrative functions. We evaluated the role of cerebellum in peripersonal defensive behavior, as assessed by the so-called hand blink reflex (HBR). Twenty subjects underwent to cerebellar (sham, anodal, cathodal) and motor cortex (anodal or cathodal) tDCS (20′, 2 mA). For the recording of HBR, electrical stimuli were delivered using a surface bipolar electrode placed on the median nerve at the wrist and EMG activity recorded from the orbicularis oculi muscle bilaterally. HBR was assessed in four different conditions: "hand far", "hand near" (eyes open), "side hand" and "hand patched" (eyes closed). While sham and cathodal cerebellar stimulation had no significant effect, anodal tcDCS dramatically dampened the magnitude of the HBR, as measured by the area under the curve (AUC), in the hand-patched and side hand conditions only, for ipsilateral ( p < 0.0001; p = 0.0008) as well as contralateral recordings ( p = 0.46; p = 0.66). tDCS applied over the motor area did not affect HBR. Our results support a role of the cerebellum in the defensive responses within the peripersonal space surrounding the face and suggesting a cerebellar involvement in visual-independent learning of defensive behavior.